Development of the flood risk map for Sungai Isap area - Khairunnisa Asyiqin, Jamaludin (2017)
Flood is the most severe natural disaster that will cause huge economic loses. Sungai Isap has experienced a disastrous flood event in 2013. Flood risk map for Sungai Isap area have been developed to reduce the impact of the monsoon flood which frequently occurred at the end of year. This flood risk map also will provide an information for the communities for rescuing and preparation on facing the flood problem during the monsoon season. The main aim of this study are to develop the flood risk map based on the flood event in year 2013 at Sungai Isap area and determine flood potential area at Sungai Isap. The selected estimation of flood risk map for this study based on elevation, likelihood and vulnerability factor which contribute most of the factor of flood event in Sungai Isap area. In this study, the flood risk map produced by using ArcGIS and Google Earth software. Google Earth software is utilized for population intensity analysis and river distance calculation while ArcGIS software is used for mapping the flood risk. Classification techniques by colour such as red, orange, yellow, light green and dark green are applied in the flood risk map to make better understanding for all the communities. The risk of flood in the study area can be identified based on the development of the flood risk map by using ArcGIS software. From the result analysis, flood potential area has been identified which is the very high risk area is located at Taman Bukit Rangin (Zone 11) and low risk area is located at Sungai Isap Satu (Zone 15).